The Impact of Physical Activity and Sport on Mental Health - abdluaziz, Tamadher; abdulaziz, Muroj (Journal of Physical Education, 2020)
Scientists have researched different aspects of physical exercise and sports and their impact on the health of a person. However, the impact of physical activity and sport on mental health has not been looked into extensively. This study reviews the literature on the effect of physical exercises and other sporting activities on mental health. The results indicate the presence of a positive link between participation in physical activities and the mental health of an individual.